2009
DOI: 10.1089/aid.2008.0188
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Distribution of HIV Type 1 Epitopes Recognized by Human Anti-V3 Monoclonal Antibodies

Abstract: Epitopes, also known as antigenic determinants, are small clusters of specific atoms within macromolecules that are recognized by the immune system. Such epitopes can be targeted with vaccines designed to protect against specific pathogens. The third variable loop (V3 loop) of the HIV-1 pathogen's gp120 surface envelope glycoprotein can be a highly sensitive neutralization target. We derived sequence motifs for the V3 loop epitopes recognized by the human monoclonal antibodies (mAbs) 447-52D and 2219. Searchin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 23 publications
2
48
0
Order By: Relevance
“…In addition, the side chain of Arg 315 of V3 forms a salt bridge with the side chain of Asp H95 . This highly specific binding of the Arg 315 side chain with a π–cation stacking and a salt bridge has led to speculation that Arg 315 is the signature motif of the epitope of 447–52D (11) . This might be the cause of 447–52D’s preference for neutralizing clade B viruses over nonclade B viruses (12) .…”
mentioning
confidence: 99%
“…In addition, the side chain of Arg 315 of V3 forms a salt bridge with the side chain of Asp H95 . This highly specific binding of the Arg 315 side chain with a π–cation stacking and a salt bridge has led to speculation that Arg 315 is the signature motif of the epitope of 447–52D (11) . This might be the cause of 447–52D’s preference for neutralizing clade B viruses over nonclade B viruses (12) .…”
mentioning
confidence: 99%
“…The analysis discussed in the current review and the constantly evolving state-ofthe-art epitope-delineation informatics approaches 30,31,[35][36][37][38] may be important for mining diverse HIV-host data, such as clinical trial data, and understanding the molecular basis underlying the effects of ADE. Further experimental assessment of the serum from patients infected during the AIDSVAX and RV144 trials may also reveal important insights into the possibility of antibody-dependent enhancement of HIV infection upon vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Many assays confirmed that the epitopes corresponding to these motifs, when expressed in the SF162 Env backbone, were sensitively and specifically neutralized by the respective mAbs. More importantly, these calculations demonstrate that globally relevant, structurally conserved epitopes are present in the sequence variable V3 loop [74]. A model for intrapartum and milk-borne HIV transmission by orally challenging neonatal macaques with chimeric simian-human immunodeficiency viruses (SHIVs) has been established.…”
Section: Monoclonal Antibodies Against Human Immunodeficiency Virus (mentioning
confidence: 99%